Oral history and memory-making in Malaysia / Hanis Diyana Kamarudin and Tom Denison - Kamarudin, Hanis Diyana; Denison, Tom (Faculty of Information Management, 2022)
The shortage of written documentation from previous authorities and colonial powers in Malaysia has accelerated the need for oral history as a method to capture valuable untold community stories. Local content history and needs of local communities in Malaysia is still not being sufficiently captured and preserved. Using the Mediated Recordkeeping Culture-as-Evidence Model as a theoretical framework, the study examines the current practice and identifies areas for improvement in oral history collections development and management in Malaysia. The evidence of this study is that oral history projects undertaken in Malaysia do not conform to a fully participatory approach, with researchers tending to regard interviewees as information providers who have little involvement in developing interview questions, program aims and outcomes. The findings in the study are crucial in providing practical suggestions for the cultural institutions that are currently involved in, or plan to take part in, oral history's collection and storage to form an ideal oral history programme for local communities in Malaysia.